Analisis Netralitas Uang Terhadap Siklus Bisnis Riil di Indonesia Periode 2011. M1- 2013. M12 - Achmad Fawaid Hasan; Sebastiana Viphindrartin; Moh. Adenan (e-Journal Ekonomi Bisnis dan Akuntansi, 2017)
The phenomenon of the neutrality of money in various countries invited economists determines its existence. Neutrality ofmoney is being debated throughout history until this time in economics. The debate became two mahzab economic is mahzabof Classic and schools of Keynes. The findings of the neutrality of money by the camp Classic, bringing new discourse ineconomics, especially monetary economics. However, the flow Keynes against the neutrality of money is also a new discoursein the field of monetary economics. The aim of the study to determine the existence of neutrality of money against economicgrowth in Indonesia, besides of simulation models goal of this study to determine the relationship of exchange rates, inflationand 1-month SBI rate to economic growth in Indonesia. The analysis method used is Ordinary Least Square (OLS) with theestablishment of model simulation and analysis of descriptive narrative. Results clause analysis with Ordinary Least Squaremethod (OLS) on model simulations indicate that the neutrality of money is not applicable in Indonesia, as well as simulationmodels in line with the 1-month SBI interest rate and the nominal exchange rate have a significant effect. While inflation stillshows the same dominant relationship. Descriptive narrative analysis gives an overview of the non-neutrality of money inIndonesia, so there needs to be an analysis or monitoring on the growth of the money supply M2.